Strategi pengembangan koperasi di era digital - Faradiba, Putri Nur (Maliki Interdisciplinary Journal, 2025)
The rapid advancement of information technology in the era of the Fourth Industrial Revolution has brought significant changes to various aspect of life, including the cooperative sector. The shift in lifestyle patterns among the millennial generation, which demands services that are fast, easy, affordable, convenient, and secure, poses new challenges for cooperatives in Indonesia. Digital transformation is a crucial factor in enhancing the competitiveness and service quality of cooperatives to remain relevant in the digital era. By utilizing online platforms, cooperatives can provide flexible access to information and services for their members. To navigate this dynamic environment, cooperatives must adapt by fostering creative and innovative characteristics among business actors as a foundation for designing organizational and business strategies aligned with the demands of Industry 4.0. This study aims to examine the importance of digital transformation in cooperatives and the role of creativity and innovation in driving their adaptation to technological developments and modern market needs.